Enabling accurate range free localization for mo-bile sensor networks - J., Kiruba; T., Rajesh (International Journal of Engineering and Technology, 2017)
The Existing localization algorithm was Sequential Monte Carlo (SMC) method for mobile sensor networks. In this paper, we propose an energy efficient algorithm called novel localization, which can achieve high localization in a better way. In existing algorithm, high Localization is achieved by getting more number of beacon nodes as input which improves the computational cost and decreases the sampling efficiency to a higher rate. But in the Proposed algorithm, we achieve high Localization accuracy with less number of beacon nodes itself thus the computational cost will be less and the sampling efficiency will be high. Our algorithm uses the approximate calculated position information of sensor nodes to increase the localization accuracy. The existing algorithms doesnâ€™t have high localization accuracy when nodes move very fast, so we have propose a new algorithm, novel localization which is executed based on spped of nodes. The novel algorithm improves the Localization accuracy also when the node move fast.Â